What drives employers' favorability ratings on employer review platforms? The role of symbolic, personal, and emotional content - Christoph E. Höllig; Andranik Tumasjan; Filip Lievens (International Journal of Selection and Assessment, 2024)
Abstract Employer review platforms have changed the recruitment landscape by allowing current and former employees to post messages about an employer outside of direct company control. Therefore, they have emerged as an important form of third-party employer branding. However, we know little about how such open-ended comments relate to the key variable in employer reviews: employers' favorability rating. Therefore, we start by situating this variable among other constructs in the employer branding space. Next, we build theory on how content in the open-ended comments of an employer review relates to the positivity or negativity of the reviews' favorability rating. We test our hypotheses via a text-mining analysis of approximately half a million employer reviews. The results reveal an intriguing discrepancy. Although instrumental, impersonal, and cognitive content is more prevalent in employer reviews, symbolic, personal, and emotional content dominates employer reviews' favorability rating. In terms of practical implications, this result shows that merely inspecting the frequency of attributes mentioned in employer review text comments as a basis for changing company policies of employer branding efforts might be misguided. We discuss implications for theory and future research, and provide our dictionary for further scholarly and practical use. Practitioners Points Employer review platforms offer insights into employee perceptions beyond an organization's control. Symbolic, personal, and emotional content, though less frequent, significantly impacts favorability ratings and should be prioritized in branding. Relying solely on attribute frequency in reviews can be misleading. Companies should analyze reviews to uncover key drivers of favorability ratings, improving recruitment strategies.
Keywords: 330; CATA; employer reviews; employer image; third-party employment branding